Quality-of-life considerations in elderly patients with bladder cancer. (December 2013) - Greco, Kristin A; Quek, Marcus L
Urothelial cell carcinoma primarily affects the elderly and may be associated with high morbidity and mortality. With the aging of the US population, therapeutic options for bladder cancer need to take into account the unique challenges of elderly patients who often have multiple associated comorbid conditions. Quality of life is now a well-recognized and important outcome measure that should be considered when deciding between the various treatments for bladder cancer. This is especially critical in the elderly patient where lengthening survival may not be the foremost goal. Treatments for both superficial and invasive bladder cancer may have an impact on quality of life, but a lack of baseline assessments in studies limits the conclusions that can be drawn. Based on available literature, quality of life in elderly patients undergoing radical cystectomy is satisfactory, regardless of whether a continent or incontinent form of urinary diversion is performed. Future prospective studies utilizing baseline assessments that include elderly patients are needed.